Integrating Functional Management Approaches for Sustainable Business Performance - Halim Tjiwidjaja (Dinasti Review, 2025)
This research explores the integration of functional management approaches to achieve sustainable business performance. The study finds that organizations that successfully integrate key managerial functions, such as finance, marketing, and human resources, create synergies that enhance operational efficiency and enable rapid decision-making. Effective collaboration and coordination between departments, supported by appropriate information technology systems, allows companies to innovate, manage risks, and build long-term relationships with customers. Moreover, regular and structured performance measurements ensure continuous improvement, helping organizations adapt to market changes and maintain sustainable business performance. This research highlights the critical role of integrated management practices in achieving not only short-term success but also long-term sustainability in the highly competitive business environment.